2020
DOI: 10.21203/rs.3.rs-19321/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning curve of digital intraoral scanning – an in vivo study

Abstract: Background: The spread of digital technology in dentistry poses new challenges and goals for dentists. It is important to involve new methods and devices in university education. The aim of the present in vivo study was to determine the learning curve of IOS described by (1) scanning time and (2) image number (count of images made by intraoral scanner during scanning process). Methods: Ten dental students of Semmelweis University took part in the study. Dental students took digital study impressions using 3Sha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Previous studies have reported the accuracy of intraoral scanners and 3D printers 17 25 . The intraoral scanner (i500; MEDIT) used in the present study for scanning of preparations and intaglio surfaces reported an accuracy of 20–30 µm with respect to a single tooth according to previous study 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the accuracy of intraoral scanners and 3D printers 17 25 . The intraoral scanner (i500; MEDIT) used in the present study for scanning of preparations and intaglio surfaces reported an accuracy of 20–30 µm with respect to a single tooth according to previous study 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The intraoral scanner has advantages of superior convenience, fast acquisition time of the virtual model, and superior accuracy (based on scanning for single unit) compared with the conventional method 22 25 . However, the use of an intraoral scanner for fixed dental prosthesis still requires a solution from a clinical perspective 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Intraoral scanners, as with any impression technique, processes a learning curve [ 35 , 36 ]. Some areas in the mouth might not be easy to capture with intraoral scanners such as the distal surfaces of the last tooth in an arch as well as the proximal surfaces near to a bounded saddle.…”
Section: Discussionmentioning
confidence: 99%
“…The intraoral scanner has advantages of superior convenience, fast acquisition time of the virtual model, and superior accuracy (based on scanning for single unit) compared with the conventional method [22][23][24][25]. However, the use of an intraoral scanner for xed dental prosthesis still requires a solution from a clinical perspective [26,27].…”
Section: Introductionmentioning
confidence: 99%